The Effect Of Socialization Of Financial Accounting Standards for Entities Without Public Accountability and MSMEs Perceptions on The Preparation Of Financial Statements - Muzayyanah Muzayyanah; Endah Nurhawaeny Kardiyati; Itat Tatmimah; Mohammad Djadjuli; Syifa Zafira Farha (Universitas Muhammadiyah Sorong, 2023)
This study aims to determine the effect of the SAK ETAP socialization on the preparation of financial statements,perception of MSMEs to the preparation of financial statements with a sample of 100 MSMEs. Research methods using descriptive quantitatif. The results of this study socialization of SAK ETAP partially positive and significant effect on the preparation of financial statements, the perception of MSMEshas a positive effect on the preparation of financial statements and the socialization of SAK ETAP and the perception of MSMEs simultaneously has a significant effect on the preparation of financial statements. With an R Square value of 85.1% shows the magnitude of the influence the level of socialization of SAK ETAP and the perception of MSMEs on the preparation financial statements, while the remaining 14.9% is influenced other factors.